2014
DOI: 10.1002/polb.23553
|View full text |Cite
|
Sign up to set email alerts
|

Confined crystallization of polymers within anodic aluminum oxide templates

Abstract: In this article, a review of recent literature on confined crystallization within nanoporous anodic aluminum oxide (AAO) templates is presented. For almost all infiltrated polymeric materials, crystal orientation within the nanopores is a function of pore diameter. T c and T m usually decrease and are a function of pore size. When no pore interconnection remains, the crystallization occur at large supercoolings in heterogeneity free environments. Hence, the nucleation mechanism changes from heterogeneous to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 97 publications
0
77
0
Order By: Relevance
“…Additionally, fractionated crystallization, possible here for iPP‐40, is often observed when the number of isolated microdomains is larger than the number of heterogeneities in the bulk polymer. Studies of other polymers inside AAO have shown that fractionated crystallization could also be caused by the presence of a polymer surface layer …”
Section: Resultsmentioning
confidence: 99%
“…Additionally, fractionated crystallization, possible here for iPP‐40, is often observed when the number of isolated microdomains is larger than the number of heterogeneities in the bulk polymer. Studies of other polymers inside AAO have shown that fractionated crystallization could also be caused by the presence of a polymer surface layer …”
Section: Resultsmentioning
confidence: 99%
“…Such a large difference normally leads to statistically clean droplets and a large depression in their crystallization temperature. For more details on the process of fractionated crystallization, the reader is referred to the literature [3,[101][102][103][104][105].…”
Section: Self-nucleation As a Tool For Ascertaining The Origin Of Framentioning
confidence: 99%
“…It is likely that it corresponds to the crystallization of a fraction of heterogeneity-free PP droplets. Its exact origin is debatable because it could correspond to the crystallization of a group of clean droplets whose nucleation either starts from the surface of the droplets (or the interface between PP and PS) or by homogeneous nucleation inside the PP droplets (see [3,[101][102][103][104][105]). …”
Section: Self-nucleation As a Tool For Ascertaining The Origin Of Framentioning
confidence: 99%
“…spatial confinement, and excellent review articles are now available for the crystallization behavior of such confined chains and resulting morphology formed in the system [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The typical nanodomains to confine polymer chains are provided by micelles in solution [3,4,13,17], aluminum anodic oxides (AAOs) [7,11,[13][14][15]18], or microdomain structures (i.e., various nanodomains formed by the microphase separation of block copolymers) [1,2,5,6,[8][9][10][11][12][13][14]16] (Fig.…”
mentioning
confidence: 99%
“…The typical nanodomains to confine polymer chains are provided by micelles in solution [3,4,13,17], aluminum anodic oxides (AAOs) [7,11,[13][14][15]18], or microdomain structures (i.e., various nanodomains formed by the microphase separation of block copolymers) [1,2,5,6,[8][9][10][11][12][13][14]16] (Fig. 1), where it is found that the crystallization behavior, final crystallinity, and crystal orientation of confined chains are extremely different from those of bulk homopolymers.…”
mentioning
confidence: 99%